2016
DOI: 10.1093/mnras/stw460
|View full text |Cite
|
Sign up to set email alerts
|

Understanding discs in binary YSOs – detailed modelling of VV CrA

Abstract: Given that a majority of stars form in multiple systems, in order to fully understand the starand planet-formation processes we must seek to understand them in multiple stellar systems. With this in mind, we present an analysis of the enigmatic binary T-Tauri system VV Corona Australis, in which both components host discs, but only one is visible at optical wavelengths. We seek to understand the peculiarities of this system by searching for a model for the binary which explains all the available continuum obse… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 61 publications
2
12
0
Order By: Relevance
“…We find the mass accretion rate for S CrA A to be ∼ 9 × 10 −8 M /yr, the mass accretion rate for S CrA B and VV CrA A to be ∼ 3 × 10 −8 M /yr, and that of VV CrA B to be ∼ 8 × 10 −8 M /yr. The derived accretion rate for VV CrA A agrees with the mass accretion rate estimate from Scicluna et al (2016) of ∼ 4 × 10 −8 M /yr, but we find that the accretion rates for S CrA A and B are lower than those measured in 2018 by Gahm et al (2018), who found that the accretion rate was ∼ 5 × 10 −7 M /yr, about an order of magnitude higher than we measure for both stars.…”
Section: Accretion Luminositysupporting
confidence: 74%
See 3 more Smart Citations
“…We find the mass accretion rate for S CrA A to be ∼ 9 × 10 −8 M /yr, the mass accretion rate for S CrA B and VV CrA A to be ∼ 3 × 10 −8 M /yr, and that of VV CrA B to be ∼ 8 × 10 −8 M /yr. The derived accretion rate for VV CrA A agrees with the mass accretion rate estimate from Scicluna et al (2016) of ∼ 4 × 10 −8 M /yr, but we find that the accretion rates for S CrA A and B are lower than those measured in 2018 by Gahm et al (2018), who found that the accretion rate was ∼ 5 × 10 −7 M /yr, about an order of magnitude higher than we measure for both stars.…”
Section: Accretion Luminositysupporting
confidence: 74%
“…We used unresolved JHKL photometry (Table 1) with our flux ratios (Table 3) to derive NIR stellar fluxes for individual components of S CrA and VV CrA. We show the component-resolved K-band (2.2µm) through Q-band (∼ 18µm) photometry of McCabe et al (2006) and Scicluna et al (2016) for S CrA and VV CrA, respectively, in Table 8. Our SEDs are shown in Figure 5.…”
Section: Sedsmentioning
confidence: 99%
See 2 more Smart Citations
“…Young multiple stellar systems were also valuable targets for MIDI observations. By determining disk geometries and orientations, cloud fragmentation and binary formation theories can be tested (Ratzka et al 2009;Roccatagliata et al 2011;Scicluna et al 2016). Tidal truncation of disks was observed in the hierarchical triple system T Tau by Ratzka (2008).…”
Section: Introductionmentioning
confidence: 99%